Water Level Forecasting at Bang Sai Arts and Crafts Center (C.29A) Gauge Station, Chao Phraya River Basin, Amphoe Bang Sai, PhraNakhon Si Ayuttaya Province Using NARX Network - Taninpong, Phimphaka; Manori, Thamonwan; Minsan, Watha (Journal of Applied Statistics and Information Technology, 2018)
This study aims to predict the water level at the Bang Sai Arts and Crafts Center (C.29A) gauge station located in the Chao Phraya River Basin, Amphoe Bang Sai, PhraNakhon Si Ayuttaya Province using NARX Network. The daily water level data at the C.13, C.3, C.7A, C.35, S.5, S.26, and C.29A gauge stations from Apr 2012 - Dec 2016 were used to develop the water level forecasting model. Data was separated in to three sets: training set, validation set, and testing set. The one-step ahead forecasting model was evaluated using mean square error (MSE), mean absolute error (MAE), and mean absolute percentage error (MAPE). The results showed that the NARX Network using only the upstream water level gauge stations and gauge station to be predicted obtained the lowest forecasting error. Moreover, the NARX model outperformed Holt-Winters forecasting method.